Last time | Next time |
We're on to Vol 1, Sec 3.9: Derivatives of exponential and logarithmic functions
The slopes of those tangents are multiplicative inverses: if the slope of one is \(m\), the slope of the other is \(\frac{1}{m}\).
\[ f'(x)=\lim_{h \to 0}\frac{f(x+h)-f(x)}{h} \] Thus \[ f'(x)=\lim_{h \to 0}\frac{e^{x+h}-e^x}{h} \] Using a property of exponentials in general, \[ f'(x)=\lim_{h \to 0}\frac{e^{x}e^{h}-e^x}{h}=\lim_{h \to 0}\frac{e^{x}(e^{h}-1)}{h} \] And, since \(e^{x}\) is independent of \(h\), we can pull it out from under the limit: \[ f'(x)=e^{x}\lim_{h \to 0}\frac{(e^{h}-1)}{h}=e^{x}\lim_{h \to 0}\frac{(e^{h}-e^{0})}{h}=e^{x}\lim_{h \to 0}\frac{(e^{0+h}-e^{0})}{h} \] But \[ \lim_{h \to 0}\frac{(e^{0+h}-e^{0})}{h} = f'(0) \] and thus \[ f'(x)=e^{x} f'(0) \] i.e. the derivative of an exponential function generally is proportional to itself, with a constant of proportionality equal to the slope of the tangent line at \(x=0\).
The value of \(e \approx 2.718281828459045\) is actually chosen because \(e\) is the particular base whose derivative at \(x=0\) is 1:
Thus \(f'(x)=e^{x}=f(x)\). This is a really incredible property!
It means that the second derivative is also \(f(x)\), and third, and fourth, and ....
So \[ \frac{d}{dx}\left(f^{-1}(x)\right) = \frac{1}{f'(f^{-1}(x))} \] becomes \[ \frac{d}{dx}\left(\ln(x)\right) = \frac{1}{e^{\ln(x)}} = \frac{1}{x} = x^{-1} \] Amazing! This derivative is the "missing power" -- we didn't know how to get this particular derivative using the power rule: it would have come from the power $x^0$ -- but that's a constant, so its derivative is 0. This creates a mysterious connection between power functions and the exponential function, and its inverse, the log.
Notice that \(\frac{1}{x}\) is our friend the hyperbola. Notice also that this function is odd -- it should be the derivative of an even function. We can extend the $\ln(x)$ function to the left, by considering $\ln(|x|)$:
This is quite an interesting function, especially as \(x \to 0\): what is \(0^0\)? That's a really interesting philosophical question!
Logarithmic differention works like this: take logs of both sides, simplify, and differentiate: \[ \ln(f(x)) = \ln(x^x) = x\ln(x) \] Therefore the chain rule on the left and the product rule on the right gives \[ \frac{f'(x)}{f(x)} = \ln(x) + x\frac{1}{x} = \ln(x) + 1 \] or \[ f'(x) = \ln(x) + x\frac{1}{x} = f(x)(\ln(x) + 1) = x^x(\ln(x) + 1) \] as seen in this image:
The population of Toledo, Ohio, in 2000 was approximately 500,000. Assume the population is increasing at a rate of 5% per year.